Impact of AGSMEIS-Funded ICT Enterprises on Poverty Reduction in Gombe State, Nigeria (2019–2025) - Ibrahim Abdullahi; Umar Farouk Musa; Mohammad Nuru Umar; Rukayya Aminu Gar (International Journal of Humanities, Education, and Social Sciences, 2026)
Access to affordable finance remains a major constraint on the growth of Information and Communication Technology (ICT) enterprises, despite the sector’s increasing importance for entrepreneurship, employment creation, and poverty reduction. The Agri-Business/Small and Medium Enterprise Investment Scheme (AGSMEIS) was introduced to address this constraint through low-interest financing and entrepreneurship training for small and medium enterprises. This study aims to examine the impact of AGSMEIS-funded ICT enterprises on poverty reduction in Gombe State, Nigeria, from 2019 to 2025. Guided by Sen’s Capability Approach and Kabeer’s Empowerment Theory, the study employed a quantitative survey design to assess the socioeconomic outcomes associated with participation in the scheme. The findings indicate that AGSMEIS-funded ICT enterprises contributed significantly to poverty reduction by increasing business income, generating employment opportunities, improving access to productive assets, and enhancing household welfare. Beneficiaries also reported improved business performance, greater income stability, and increased capacity for enterprise expansion. However, inadequate electricity supply, inflation, and weak digital infrastructure constrained the extent to which beneficiaries could realize the full benefits of the programme. The study concludes that AGSMEIS has positively contributed to poverty reduction among ICT entrepreneurs in Gombe State by strengthening income-generating capacity and supporting enterprise development. These findings contribute to the literature on development finance, financial inclusion, and entrepreneurship by demonstrating the poverty-reduction potential of targeted SME financing in the ICT sector. The study further highlights the need to strengthen post-loan support services, improve digital infrastructure, and expand access to ICT-focused financing to enhance the effectiveness and sustainability of similar interventions.